Enhancing the quality of life of coastal community through ecotourism development in Kota Marudu, Sabah - Musa, Fazilah; Abd. Ghani, Awang Noor; Mohd, Abdullah (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Mangrove ecosystem provides important benefits to the society which comprises provisioning, regulating, cultural and supporting services. In Kota Marudu, Sabah, the mangrove ecosystem is an important support system for fishery resources and significant contribution to sustainable income for coastal community. However, its role in ecotourism development for long term benefits has yet to be identified and planned. Many of the mangrove ecosystem resources including forests, rivers, sea, fisheries and local culture can be further developed into ecotourism products which can enhance income and quality of life of the coastal community. The development of community-based ecotourism (CBE) in Kota Marudu seems to be promising due to availability of these resources, willingness to participate by coastal community, strong support from the government and NGOs and strong linkages between the university, local community and government departments. The implementation of CBE entails active community participation at all levels of designing, planning, implementation and evaluation of ecotourism activities and these skills are lacking or nonexistent in Kota Marudu. This project aimed to enhance ecotourism skills of coastal community so that they can take initial step in formulating and planning ecotourism development in Kota Marudu of mangrove ecosystem. Training of participants in ecotourism involved selected households from eight coastal villages. Training modules were prepared by UPM experts in ecotourism planning, mangrove ecosystem and biodiversity, wildlife, social and economics and marine biology. The training session involved face to face class discussion, visit to potential mangrove ecotourism sites and group discussion. Some challenges in the project are willingness of the local community to continue the project, the level of understanding of community-based ecotourism, cooperation among the local community in ecotourism planning and implementation, lack of infrastructure facilities, demand for ecotourism by local and foreign tourists, market competition of mangrove ecosystem and other popular destinations and incentives by the government. Strong commitment towards knowledge transfer program by UPM researchers is needed to realise ecotourism development in Kota Marudu.